STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI APPARALANG SEBAGAI DAERAH TUJUAN WISATA KABUPATEN BULUKUMBA - sri wahyuningsih; Mahmud Nuhung; Ismail Rasulong (Universitas Muhammadiyah Makassar, 2019)
The data collection technique used is library research. This study aims to determine the opportunities for developing tourism objects in Apparalang Beach in Bulukumba Regency and to find out strategies that can be done by the government in developing tourism objects in Apparalang Beach in Bulukumba Regency. This type of research is qualitative descriptive, which is an analysis used to systematically describe or solve problems using the SWOT analysis method, namely the analyst in question to see how far the application of tourism development strategies in increasing tourists based on strengths, weaknesses, needs, and threats. The strategy adopted by the tourism agency is a position to maintain and maintain. This condition is key in determining strategies that might be developed in market penetration and development of products that are in accordance with the conditions of the tourism agency of Bulukumba Regency. The three main strategies that are produced are conducting socialization of Sapta Pesona or penyadara benefits of tourism for all levels of society in a sustainable and systematic manner, development of community-based tourism, and tourism HR services must have tourism certification